The marriages and love lives of Spanish and American soldiers in the Costa Firme wars of Independence - Pita Pico, Roger (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2022)
Few attempts have been made to systematically and exhaustively investigate topics such as the expression of feelings or endeavours to get married or be close to loved ones in the midst of war. Within the framework of the new military history and the commemoration of the bicentennial of the independence of the Spanish-American world, these were precisely the subjects that inspired the present article. Defining the spatial context as the territory known in that period of war as Costa Firme, which included the jurisdiction of New Granada and Venezuela, this study focuses on Spanish soldiers, Creoles serving in the Spanish regime’s attempt to retain its dominance over these New World territories, and the military forces organised by the Republicans in an effort to gain definitive freedom from Spain.